PERLINDUNGAN HUKUM BAGI KORBAN BULLYING DI LINGKUNGAN SEKOLAH - Qomariah, Qomariah (Legal Studies Journal, 2024)
Lately, news about bullying cases in Indonesia has increased. bullying continues to colour the world of education in Indonesia. this must be very worrying for the condition of the victims, especially for children who are still in school, they can only surrender and cannot fight against bullies. So, the purpose of this research is to analyse, study, and get to know the legal protection that can be received by victims of bullying and know how to prevent and reduce cases of bullying. In this writing, a normative research method is used, which focuses on the study of legal materials. The approach applied is the statute approach, which is carried out by referring to relevant rules and regulations. The results of this paper explain the existence of legal protection that can be given to children who are victims of bullying as well as how to prevent and reduce cases of bullying. settlement through legal channels is the last step in bullying cases and requires continuous cooperation by all parties starting from oneself, family, school, and the state. prevention of bullying from an early age is certainly very important through moral education, the application of living together full of kinship and responsibility is an effective first step to reduce bullying in the school environment.